Asymmetric Inner-Core Structure and its Impact on Rapid Intensification of a Sheared Tropical Cyclone - Liu, Bojun; Wang, Mingjun; Zhao, Kun (Frontiers in Earth Science, 2022)
Based on ground-based Doppler radar data with high spatial and temporal resolution, our study focuses on rapid intensification (RI) of a sheared tropical cyclone (TC). The asymmetric inner-core structure and its impact on RI are presented using the Advanced Regional Prediction System-3DVAR. The time evolution of the TC inner-core characteristics shows that Meranti experiences two stages of RI: the asymmetric dominant period and the axisymmetric dominant period. The comparison between the two RI stages shows that the vortex intensified more in the asymmetric stage than the axisymmetric stage. The wavenumber-1 component introduced by the vertical wind shear dominates the asymmetric structure. In the moderate-to-strong shear environment, deep convection occurs mainly in the downshear-left quadrant, generating substantial diabatic heating in the downshear region. Under a suitable inner-core structure configuration, the downshear vortices are entrained cyclonically inward, resulting in RI. This is the interaction between the axisymmetric inner-core structure of the TC and the mesoscale vortex that controls the intensification process, which can be replicated by the nondivergent barotropic model with a similar initial field. This infrequent case provided observation of RI during a strong shear period, which suggests that the inner core structure is vital for TC RI.